2022
DOI: 10.3389/fpls.2022.934379
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Profiling of DNA Methylome and Transcriptome Reveals Epigenetic Regulation of Potato Response to DON Stress

Abstract: Potato is an important food crop that occupies lesser area but has greater production than rice and wheat. However, potato production is affected by numerous biotic and abiotic stresses, among which Fusarium dry rot is a disease that has significant effect on potato production, storage, and processing. However, the role of DNA methylation in regulating potato response to Fusarium toxin deoxynivalenol (DON) stress is still not fully understood. In this study, we performed DNA methylome and transcriptome analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…As reported in existing studies, DON induction can enhance plant defense by regulating the gene expression of SA and JA pathways, causing SA accumulation and activation of pathogenesis-related genes (PR) [55]. Therefore, we hypothesize that DON induces plant defense through the interaction of SA and JA signaling, and that this process is regulated by DNA methylation [43,56].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…As reported in existing studies, DON induction can enhance plant defense by regulating the gene expression of SA and JA pathways, causing SA accumulation and activation of pathogenesis-related genes (PR) [55]. Therefore, we hypothesize that DON induces plant defense through the interaction of SA and JA signaling, and that this process is regulated by DNA methylation [43,56].…”
Section: Discussionmentioning
confidence: 70%
“…Our previous study found that treatment of potato tubers with low concentrations of DON also affected resistance to late blight caused by P. infestans [43]. However, the effects of fungal toxins on potato tuber resistance and the relationship between resistance and transcriptional and metabolic changes have not been reported, and the molecular basis and physiological and biochemical changes in potato-induced resistance under DON induction are not clear.…”
Section: Introductionmentioning
confidence: 97%